2003
DOI: 10.1104/pp.010538
|View full text |Cite
|
Sign up to set email alerts
|

In Plants, 3-O-Methylglucose Is Phosphorylated by Hexokinase But Not Perceived as a Sugar

Abstract: The dynamics of polyribosome abundance were studied in gravistimulated maize (Zea mays) stem pulvini. During the initial 15 min of gravistimulation, the amount of large polyribosomes transiently decreased. The transient decrease in polyribosome levels was accompanied by a transient decrease in polyribosome-associated mRNA. After 30 min of gravistimulation, the levels of polyribosomes and the amount of polyribosome-associated mRNA gradually increased over 24 h up to 3-to 4-fold of the initial value. Within 15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 58 publications
1
38
0
1
Order By: Relevance
“…The variable eVects of sugars and its analogs on the expression of diVerent genes could be attributed to the activation of diVerent components of sugar mediated signaling pathways (Sinha et al 2002). Although palatinose and turonose are not transported, 3-OMG, which is transported across the membrane (Cortes et al 2003) and can regulate the expression of (c, d). Samples were harvested 1, 3, 6, 12, 24, 48 or 72 h after transfer.…”
Section: Metabolically Active Sugar Is Required For the Induction Of mentioning
confidence: 98%
“…The variable eVects of sugars and its analogs on the expression of diVerent genes could be attributed to the activation of diVerent components of sugar mediated signaling pathways (Sinha et al 2002). Although palatinose and turonose are not transported, 3-OMG, which is transported across the membrane (Cortes et al 2003) and can regulate the expression of (c, d). Samples were harvested 1, 3, 6, 12, 24, 48 or 72 h after transfer.…”
Section: Metabolically Active Sugar Is Required For the Induction Of mentioning
confidence: 98%
“…Very rapid gravity-specific changes in transcript abundance have been documented in gravistimulated root tips of Arabidopsis (Arabidopsis thaliana; Kimbrough et al, 2004) and in whole seedlings (Moseyko et al, 2002). Additionally, Heilmann et al (2001) have demonstrated that specific transcripts are selectively recruited into polysomes of maize (Zea mays) pulvini within 15 to 30 min of gravistimulation, and Young and Masson (2004) have shown that rapid changes in protein distribution occur within 12 to 30 min of gravistimulation in Arabidopsis roots. These results indicate that transcriptional and translational regulation is also involved in the early signaling events.…”
mentioning
confidence: 99%
“…Previous gene-specific and genome-wide studies of translational control make it increasingly clear that differential translation of mRNA species occurs in plants under a range of situations, including abiotic stresses (Kawaguchi et al 2004, Branco-Price et al 2008, Matsuura et al 2010, changes in light availability (Juntawong and Bailey-Serres 2012) and gravistimulation (Heilmann et al 2001). Differential translation also occurs among distinct cell types (Mustroph et al 2009) and among different stages of plant development (Jiao andMeyerowitz 2010, Liu et al 2012).…”
Section: Introductionmentioning
confidence: 99%